Methionine sulfoxidation of the chloroplast small heat shock protein and conformational changes in the oligomer. - Gustavsson, N. (Cold Spring Harbor Laboratory Press, 1999)
The small heat shock proteins (sHsps), which counteract heat and oxidative stress in an unknown way, belong to a protein family of sHsps and alpha-crystallins whose members form large oligomeric complexes. The chloroplast-localized sHsp, Hsp21, contains a conserved methionine-rich sequence, predicted to form an amphipatic helix with the methionines situated along one of its sides. Here, we report how methionine sulfoxidation was detected by mass spectrometry in proteolytically cleaved peptides that were produced from recombinant Arabidopsis thaliana Hsp21, which had been treated with varying concentrations of hydrogen peroxide. Sulfoxidation of the methionine residues in the conserved amphipatic helix coincided with a significant conformational change in the Hsp21 protein oligomer.